COVID-19 and pregnancy: a comprehensive study of comorbidities and outcomes - Shang-Ming Zhou; Hossein Ahmadi; Lin Huo; Lisa M. Lix; Kate Maslin; Jos M. Latour; Jill Shawe (BMC, 2024)
Abstract Objectives This study aimed to investigate the impact of pregnancy and pre-existing comorbidities on COVID-19 infections and associated complications of hospitalisation and mortality in women of reproductive age (WRA). The study also compared the risk of severe COVID-19 complications between pregnant women (PW) and non-pregnant women (NPW) with and without pre-existing comorbidities. Special focus was placed on some understudied comorbidities of immunosuppression, chronic renal disease and chronic obstructive pulmonary disease (COPD). Methods The study utilized anonymized patient-related information for a population of 7,342,869 WRA from the Mexican Ministry of Health data repository on COVID-19. Descriptive variables were characterized using frequencies, percentages, means, and standard deviations. Adjusted odds ratios (aORs) were used to assess the associations between risk factors and outcomes of hospitalisation and mortality. The study covered the entire COVID-19 pandemic period from January 30, 2020, to May 5, 2023. Results The findings revealed that PW were not more likely to get COVID-19 infections than NPW. PW with COVID-19 infections were more likely to require hospital admission, intubation treatments, and ICU admission compared to NPW with COVID-19. PW with immunosuppression had an increased odds ratio (aOR) of getting COVID-19 infections compared to NPW (PW: aOR = 1.0396; NPW: aOR = 0.8373). NPW with immunosuppression had higher risk of mortality (all-cause death: aOR = 1.7084; COVID-19-associated death: aOR = 1.4079) and hospitalisation (all-cause hospitalisation: aOR = 4.1328; COVID-19-associated hospitalisation: aOR = 3.0451) than NPW without immunosuppression. Renal disease was identified as a concerning pre-existing condition that increased the risks of COVID-19 associated mortality/hospitalizations and all-cause mortality/hospitalizations for both PW and NPW. NPW with renal disease had much higher odds ratio (aOR) of either COVID-19-associated-hospitalisations (NPW: aOR = 8.639; PW: aOR = 1.7603) or all-cause hospitalisations (NPW: aOR = 8.8594; PW: aOR = 1.786) than PW with renal disease. Conclusions This study provides valuable insights into the impact of pregnancy and pre-existing comorbidities on COVID-19 outcomes in WRA. The findings underscore the importance of considering demographic factors and pre-existing comorbidities in the management of PW with COVID-19. The study also highlights the need for further research to understand the unique impacts of different comorbidities, particularly immunosuppression and renal disease, on COVID-19 outcomes in WRA.